Establishing foreign bookshelves in libraries around the world: a socio-cultural component of international cooperation - Demianiuk Liudmyla (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to examine the strategic initiative of establishing special bookshelves for foreign literature in libraries around the world, emphasizing their sociocultural impact as an element of international cooperation. The research methodology is based on a systematic approach, methods of logical and structural-functional analysis, generalization, and content analysis. Scientific novelty. An analysis of the "Ukrainian Bookshelves" project has been conducted, aimed at promoting Ukrainian literature worldwide and fostering global cultural understanding. Additionally, the study highlights the experience of organizing bookshelves for foreign literature at V. I. Vernadskyi National Library of Ukraine, illustrated by the recent "Polish Bookshelf in Ukraine" project (2023), as well asthe "Liechtenstein Bookshelf" (2004) and the "Switzerland Bookshelf" (2014),which operate within the Department of International Information and ForeignRelations at V. I. Vernadskyi National Library of Ukraine. The research has found that such projects are effective tools of cultural diplomacy that significantly enhance global cultural understanding. Conclusions. In the current geopolitical and cultural context, a pressing issue for Ukraine is the preservation of the identity of the Ukrainian nation and its cultural heritage for future generations. It is necessary to increase the visibility of Ukrainian culture and literature on the international stage and to promote the development of mutually beneficial international relations through the launch of similar initiatives. The strategic implementation of these endeavors underscores the importance of libraries in fostering global understanding and maintaining meaningful international relations, significantly contributing to the preservation and promotion of national identity in an international context. The potential of such library projects in building bridges between cultures, promoting deeper mutual respect and cooperation is emphasized.